Digital Diplomacy and US Consular Assistance - K. E. Petrov (Международная аналитика)
The paper discusses the digitization of diplomacy and the consular assistance at the present stage of the communication technologies development. Globalization, and especially the rapid development of the mass media and social media has affected almost every citizen. This process allowed the Foreign offices to come closer to resolving the issue of smart personal communication with nationals who are abroad. The first part of the paper analyzes the possibilities of using the power of the modern social media by the Ministries of foreign affairs to create and maintain effective crisis communication. The second part of the article focuses on the analysis of a digital consular assistance to nationals at home and abroad using the example of a specialized application created by the US Department of State.